Supporting consumer choices toward healthy, safe and sustainable diets in low and middle-income countries - Ruben, Ruerd; Grace, Delia; Lundy, Mark M. (International Food Policy Research Institute, 2020)
Food systems and diets are transforming rapidly in many parts of the world, particularly in low- and middle-income countries (LMIC). Changes in income, employment, taste, and location have direct implications for food choices and shopping patterns, which in turn have impacts on consumers’ nutrition and health, as well as environmental sustainability and resilience of the food system.